Risk factors of laryngeal cancer in patients attended in the oral oncology center of Araçatuba - Marcelo Coelho Goiato; Aline Úrsula Rocha Fernandes (Universidade Estadual de Campinas, 2015)
The laryngeal cancer is the second most common respiratory cancer worldwide. The aim of this study is to perform a survey on data related to the incidence of laryngeal cancer that would enable its analysis among patients with larynx cancer attended at the Oral Oncology Center from the Dentistry School - UNESP, Araçatuba-SP-BR. Out of the 66 cases of cancer registered at the Oncologic Treatment Center between 1991 and 2003, 64 cases were identified in men. Information of gender, age, race, tobacco and alcohol use and occupational history were obtained from patients through a standardized questionnaire. The largest number of cases of laryngeal cancer occurred among farmers, building constructions workers and drivers. The incidence was higher among smokers, white individuals with ages ranging from 50 to 60 years. In conclusion, the risk of laryngeal cancer was associated to several factors, also occurring due to the effect of the socio-economic status, diet, income and educational level.